Cost-benefit analysis of working with recovery in river management using Marxan - Agnew, Danelle; Fryirs, Kirstie; Leishman, Michelle R. (Frontiers in Environmental Science, 2024)
With the impact and cost of continued river degradation and climate change-induced extreme rainfall and floods, there is growing urgency to achieve and maintain good river health to meet global sustainable development goals. Up-scaling and working with nature-based solutions at regional, catchment and fluvial corridor scales is critical. One way to achieve this is to work within a recovery-enhanced approach to river rehabilitation, incorporating processes of geomorphic and vegetative recovery to build fluvial corridors in areas where they have become fragmented. Geomorphologically-informed cost-benefit analysis has not previously been applied in a riverine or riparian context, at the catchment or regional scale needed. We applied Marxan in a novel manner to undertake the first cost-benefit analysis for geomorphologicallyinformed rehabilitation of river systems. We estimated that to rehabilitate 75,500 km of streams in coastal catchments of NSW will cost $8.2 billion, comparing favourably to recent single flood event insurance losses, and projected future losses. We developed Marxan scenarios based on three broad approaches to river management: 'ad hoc and reactive', 'working with recovery' and 'corridors', across current and future time periods. We found there are considerable current and flow-on future financial and non-financial benefits, and lower initial total and per-hectare rehabilitation costs, by fully adopting 'working with recovery' or 'corridors' approaches and moving away from the 'ad hoc and reactive' approaches which dominate current practice. Implementing targeted rehabilitation based on a rolling sequence over time of 'corridors' scenarios provides optimal holistic solutions to improve geomorphic condition and enhance recovery potential at landscape-scale. Our study demonstrates the use of Marxan as an accessible tool to address prioritisation complexity, and to run and cost landscape-scale rehabilitation scenarios over time. Our study also demonstrates the positive offsite feedbacks that occur through multiplier effects, as recovery occurs, and corridors are built. Geomorphologically-informed decision making becomes more robust, transparent, costeffective, consistent across catchments, and adaptive to local situations and evolving river management priorities.